Enhancement of blood flow containing tri-nanoparticles between bent peristaltic conduit and endoscope via thermal radiation and magnetic resonance - Awatif J. Alqarni; Essam M. Elsaid; Mohamed R. Eid; Mohamed S. Abdel-wahed (Alexandria Engineering Journal)
Heat features of a ternary nanofluid are examined in a heated flowing condition among a curvy conduit and endoscope that undergo peristalsis motion and sinusoidal variabilities. Three nanoparticles, copper, silver, and aluminum oxide were dispersed in blood as a basic fluid to study their potential effects on the flow and temperatures of the mixed fluid under thermal radiation and magnetic resonance, as well as the system's entropy optimization. The authors explored this system to understand flowing and heat diffusion in peristaltic conduits and as a medical application that may offer a future perspective for all researchers. Continuity and energy equations in their partial differential form related to the Maxwell equation due to the influence of radial magnetic force determined issue modeling based on basic regulating equations. This system was simplified by assuming a long wavelength and translated to ODEs using similarity. Closed-form solutions in magnetic fields were calculated using Mathematica software. Comparing results to earlier studies proved validity. Figures and tables showed how the issue factors affected pumping, temperature, pressure gradient, and heat transfer rate. The most significant findings record that the boluses density climbs considerably and the pressure gradient grows up as the magnetic resonance and gab ratio increases. Data Availability: Manuscript has no associated data.